CURRENT STATE AND PRODUCTIVITY OF OAK STANDS IN UKRAINIAN POLISSYA - Lakyda, P. I.; Bala, O. P.; Matushevych, L. M.; Ivaniuk, I. D. (Forestry and Forest Melioration, 2018)
Introduction Currently, the productivity, stability and reproductive ability of oak stands of Polissya are reducing. Depending on site conditions pine forests is dominating, in places mixed with birch and aspen. As part of this work, it was expected to research patterns of growth and development of oak stands that will enable building up the concept of restoration of forest and ecological potential of the oak stands. Materials and Methods Data analysis was made based on "Subcompartment characteristics of the forest" relational database. The research was conducted using the methods of comparative analysis of the classic forest mensuration approaches involving methods of mathematical statistics. Results In Ukrainian Polissya, the total area of forest stands containing oak is 334,376.5 hectares. The largest areas of oak stands are in Zhytomyr region (35.3 %). The oak forests in Chernihiv (16.4 %) and Volyn (14.7 %) regions are almost two times less. In the other regions: Kiev, Lviv, Rivne, Sumy, Khmelnytsky, oak forest areas are in the range from 1.9 to 9.4 %. The stands of natural origin represent the largest percentage of the forests (43.9%). The share of artificial oak stands is 38.6 % and of vegetative origin stands, 17.5 %. Artificial oak plantations dominate in Sumy, Khmelnytsky and Chernihiv regions (44.4, 59.3 and 40.0 %, respectively). The largest areas of plantations of vegetative origin are located in Sumy, Kyiv and Chernihiv regions (38.0, 24.8 and 23.0 %, respectively). The natural origin stands dominate in Lviv and Rivne regions (54.4 and 57.5 %, respectively). On the territory of Ukrainian Polissya, pure oak stands occupy the little area and reach 8.4 % only. The age classes of the oak stands range from I to XX, but the age structure of the stands is far from the optimum. The majority of oak forests in all investigated areas of Polissya belong to the age classes VII (17.6 %), VI (16.1 %), VIII (13.5 %), V (9.5 %) and IX (7.6 %). The oak stands of other age classes occupy an area of about 5 % or less. There are high productivity oak forests of mostly I–II site class (77.4%) in Polissya region. High productivity oak stands of Ia site class and upper classes, as well as low productive stands of IV class and lower classes, are rare; their total area percentage is 2.8 and 3.3 %, respectively. Stand density of the oak forests is mainly medium, with the dominating relative density index of 0.7 both generally (40.9 %) and in each administrative region (from 34.1 to 44.6 %). At the Polissya of Ukraine, the overwhelming majority of the oak stands, with a share of 52.7 %, growth in moist fairly fertile sites; 25.8 % of them are in fresh fairly fertile sites. Fresh and moist fairly infertile pine site types, as well as fresh and moist fertile site types, are more rarely for the oak stands; their percent is 9 and 11.2%, respectively. The evaluation of average inventory characteristics is important for the analysis of state and productivity of oak stands in Ukrainian Polissya. The data analysis shows that, within the administrative regions of Polissya, the oak stands mainly are middle aged (of age classes VII–VIII), of middle stand density (0.64–0.71) and of high productivity (site classes I–II). They have the average diameter from 18.1 to 21.6 cm, the average height from 23.3 (site class II) to 26.7 m (site class I) and stand volume from 175 m3·ha-1 (site class II) to 246 m3·ha-1 (site class I). The average age of the oak forest stands ranges from 25 to 45 years in infertile pine sites with different moisture, from 54 to 101 year in fairly infertile pine sites, from 44 to 74 years in fairly fertile conditions, and from 42 to 72 years in fertile site conditions. This age distribution by types of oak forest site indicates the small area of mature oak forests remaining. Similarly, the area of young stands is insignificant too, especially of age classes I and II. Conclusions Analysis of the current state and productivity of oak stands of Ukrainian Polissya provides an estimation of forest and environmental potential of oak stands as well as of their capabilities to natural and artificial regeneration in different types of forest sites under climate change.